A real-time loop-mediated isothermal amplification assay for rapid detection of shigella species - Liew, P.S.; Teh, C.S.J.; Lau, Y.L.; Thong, Kwai Lin (The Malaysian Society of Parasitology and Tropical Medicine, 2014)
Shigellosis is a foodborne illness caused by the genus Shigella and is an important global health issue. The development of effective techniques for rapid detection of this pathogen is essential for breaking the chain of transmission. Therefore, we have developed a novel loop-mediated isothermal amplification (LAMP) assay targeting the invasion plasmid antigen H (ipaH) gene to rapidly detect Shigella species. This assay could be performed in 90 min at an optimal temperature of 64 degrees C, with endpoint results visualized directly. Notably, the method was found to be more sensitive than conventional PCR. Indeed, the detection limit for the LAMP assay on pure bacterial cultures was 5.9 x 10(5) CFU/ml, while PCR displayed a limit of 5.9 x 107 CFU/ml. In spiked lettuce samples, the sensitivity of the LAMP assay was 3.6 x 10(4) CFU/g, whereas PCR was 3.6 x 10(5) CFU/g. Overall, the assay accurately identified 32 Shigella spp. with one enteroinvasive Escherichia coli displaying positive reaction while the remaining 32 non-Shigella strains tested were negative.